Recovery Plan for Bentinckia Condapanna Berry - an Endemic and Threatened Tree Species (palm) of Tropical Semi- Evergreen forests in Southern Western Ghats, India - Basu, Aruna; Sarkar, Manoj Kumar; Muthukrishnan, A.; Arockiasamy, D. I. (Indian Forester, 2014)
Bentinckia condapanna Berry is one of the endemic and threatened tree species (palm) of the Southern Western Ghats in Peninsular India. B. condapanna and B. nicobarica (Kurz) Becc. are the two species of this family enlisted as threatened species of genus Bentinckia by Botanical Survey of India during 1988. B. condapanna has narrow endemic zone of distribution in the hills of South Travancore and Tirunelveli Hills of Tamil Nadu and Kerala. The habitats of the species in Tamil Nadu particularly in Kalakad Mundanthurai Tiger Reserve were analysed using GPS, GIS and stratified random sampling techniques. Satellite remote sensing data with the aid of GIS were used for site-specific mapping of the threatened species, the status of niches with regard to its growth and degradation. The threat status of the species was reassessed. Growth habit, botanical description, silvicultural characters, ethnobotanic and other utility of the species are provided. The places of endemism, precise point-location data, the phyto-geographic parameters of the area and its phytosociological layout are illustrated. Immediate need to protect and propagate this endangered species is emphasized and its methods of artificial reproduction elaborated. Finally, Threatened Species Recovery Plan (TSRP) has been suggested to protect and promote the species using in-situand ex-situ conservation methods.